Pergeseran Nilai pada Tradisi Makan Bajamba di Nagari Koto Tangah Kecamatan Tilatang Kamang Kabupaten Agam - Safarra Fitri Rahmatika; Febri Yulika; Hijratur Rahmi (Ethnography : Journal of Cultural Anthropology, 2021)
This study discusses the change in Bajamba`s eating tradition values in Koto Tangah village, Tilatang Kamang District, Agam Regency, West Sumatra Province. The method used is qualitative research method by using descriptive analysis. Theory of social systems in Talcott Parsons' thought is used in this research. Bajamba`s eating is a tradition of eating in a marriage ceremony from the ancestors of the ancestors. Bajamba is eating on a large plate together consisting of five to seven people. Eating Bajamba aims to foster friendship and create a sense of togetherness among relatives regardless of social status. The tradition of eating bajamba has ethics and procedures that generally already exist. The purpose of this study was to determine the form of the process of implementing bajamba eating in the Koto Tangah village, to determine the shift in the value of the bajamba meal in the Koto Tangah village, Tilatang Kamang district, Agam regency. The results of the study show that the procedure for eating bajamba in the Koto Tangah village is still being carried out now. However, eating bajamba experiences a shift in value in its implementation. The Bajamba eating tradition itself is caused by technological, globalization, and economical factors.